Prospects for extraction of energy resources in astroblems of Ukraine - Bagriy, I.; Hafуch I.; Payuk, S.; Solodkyy, E.; Yaroshovets-Baranova, K. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Analysis of the results of complex studies of the structure and prospects of oil and gas bearing impact structures (astroblems) of Ukraine are based on the introduction of the latest technologies and equipment complexes. The purpose of the research is to assess the prospects for the production of energy resources in the astroblems of Ukraine (hydrocarbons, oil shale, brown coal, hydrogen, helium) according to the STHAGC. The paper is based on the factual material made up of the results of many years of field surveys performed according to the integrated practice of structural, thermal, hydrological, atmogeochemical surveys (STHAGC) of the impact structures. This technique has proved successful as a practical tool for prospecting of mineral reserves (hydrocarbons, underground waters) and solution of ecological problems in various regions of Ukraine (the land and water areas of the Black Sea and the Sea of Azov). Impact structures (astroblems) should be regarded as non-traditional sources of the energy feedstock, namely, oil and gas. Prospecting and operation of these sources will permit to significantly enlarge the energy potential within the shortest time and strengthen the national security of the country. The main targets of the surveys performed by the monograph authors were the following impact structures in Ukraine: Bovtyska and Obolonska. The Bovtyskа structure is proposed as a primary object for purposeful geological exploration.